Supporting Microscopy Learning with Ocul-AR, a Virtual and Augmented Reality-Powered Mobile Application - Pylvänäinen Joanna W.; Mairinoja Laura; Tuomisto Tino; Solis Junel; Toivola Diana M.; Kankaanpää Pasi (Germany, 2025)
Microscopy has become an irreplaceable tool for visualizing, analyzing and quantifying life in several research fields, such as cell biology and tissue diagnostics. However, to acquire optimal imaging of a sample, the microscope needs to be correctly operated. While microscopes are available in many research institutions and laboratories, they often lack proper user and calibration instructions. Online training materials have become important, but their content is usually generic, microscope-specific information is unavailable, and they cannot help users onsite. Therefore, specific microscopy skills are normally transferred from person to person, which in turn leaves space for subjective errors that can accumulate over time. To meet these challenges, we developed a mobile application, Ocul-AR, for microscopy teaching and support. Ocul-AR was designed by a multidisciplinary team to guide microscopy students and users to learn about microscopy, optimize light paths and operate light microscopes independently. To investigate the usability and relevance of the application in higher education, a voluntary test group was collected from a university introductory-level microscopy course, and the Ocul-AR application was tested in separate sessions during and after the guided hands-on training of the course. Volunteers were surveyed about their experiences before, during and after the handson training. All respondents (n=11) reported that Ocul-AR helped them to learn hands-on microscopy (64% replied that the application helped definitely, 36% that it helped somewhat), as well as helped them to recall microscopy skills (90% definitely, 10% somewhat). Students who used Ocul-AR during the course felt they gained confidence to operate the microscope during the hands-on session (82% definitely, 18% somewhat) and that it lowered their threshold for using the microscope independently (70% definitely, 30% somewhat). Overall, in this article, we show that the Ocul-AR application offers useful solutions to challenges in microscopy teaching and guidance, as well as promotes learning microscopy in a higher education context.
Proceedings of the Technology-Enhanced Learning in Laboratories workshop (TELL 2023), April 27, 2023, Online